(untitled) (ModaPalavra e-periódico, 2016)
This text presents stories about the patrimonialisation process of the clothing collection from the Traditionalist Gaucho Movement (Movimento Tradicionalista Gaúcho, MTG), located in the city of Porto Alegre, Rio Grande do Sul. The collection is described by the interlocutors who narrate their daily experiences as participants in the process. This set of information weaves a form of storytelling, whose intention is not to rebuild the narratives in a linear and chronological way, but in a way that is plural, multiple and fragmented. Still, the research is based on written sources, such as documents, photographic records andfield Journals accessed during the empirical research conducted in the years 2014 and 2015. By highlighting the memories, the knowledge and the trajectories from the interlocutors at the collection, it was possible to understand that the clothing is a part of who they are and it sets outto open their ideals and wills.